(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2019)
How does the municipal platform Beirut Madinati challenge relations of subordination through its nuanced facilitation of radical democratization processes in Beirut and beyond? Drawing on in-depth, semi-structured interviews with electoral candidates, founders and volunteers of Beirut Madinati and an analysis of documents provided by the participants, this study argues that Beirut Madinati has facilitated nuanced processes of radical democracy, which can disrupt patron-client relationships and challenge sectarianism, by attempting to advance egalitarian political structures through the enhancement of participation for and representation of Beirut’s diverse population. In particular, the Lefebvrian Right to the City approach implemented by Beirut Madinati through its various activities is a practical example of radical democracy. For example, the municipal platform organizes residents through its Neighborhood Groups to demand public goods and service provision from the municipality instead of being dependent on local chapters of sectarian political parties. At an institutional level, Beirut Madinati’s Alternative Municipality functions as a shadow municipality, which keeps officials and sectarian political parties accountable. Its Electoral Working Group, on the other hand, pursues political mobilization countering the sectarian political establishment attempting to build an independent labor union movement and co-creating a national coalition compromising civil society groups and independent parties for the 2018 parliamentary elections in Lebanon. The research explores Beirut Madinati’s role and impact at a national and global level examining specifically the transnational character of municipal platforms, which are able to frame local everyday struggles in a global context.